Morphological and enzymatic analysis of the midgut of Anopheles darlingi during blood digestion - Okuda, K.; Caroci, A.; Ribolla, P.; Marinotti, O.; de Bianchi, A. G.; Bijovsky, A. T. (Elsevier B.V., 2005)
The midgut of adult female Anopheles darlingi is comprised of narrow anterior and dilated posterior regions, with a single layered epithelium composed by cuboidal digestive cells. Densely packed apical microvilli and an intricate basal labyrinth characterize each cell pole. Before blood feeding, apical cytoplasm contains numerous round granules and whorled profiles of rough endoplasmic reticulum. Engorgement causes a great distension of midgut. This provokes the flattening of digestive cells and their nuclei. Simultaneously, apical granules disappear, the whorls of endoplasmic reticulum disassemble and 3 h post bloodmeal (PBM), nucleoli enlarge manyfold. An intense absorptive process takes place during the first 24h PBM, with the formation of large glycogen inclusions, which persist after the end of the digestive process. Endoproteases activities are induced after bloodmeal and attain their maximum values between 10 and 36 h PBM. At least two different aminopeptidases seem to participate in the digestive process, with their maximum activity values at 36 and 48 h PBM, respectively. Coarse electrondense aggregates, possibly debris from digested erythrocytes, begin to appear on the luminal face of the peritrophic membrane from 18 h PBM and persist during all the digestive process, and are excreted at its end. We suggest that these aggregates could contain some kind of insoluble form of haem, in order of neutralize its toxicity. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Anopheles darlingi; midgut; mosquito; ultrastructure; protease